HUBUNGAN ANTARA SELF-CONFIDENCE DENGAN TINDAKAN ACADEMIC DISHONESTY PADA MAHASISWA PENGGUNA CHATGPT - Tasya Viviana; Sandi Kartasasmita (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
This study aims to examine the relationship between self-confidence and academic dishonesty among university students who use ChatGPT. Amid the increasing use of Artificial Intelligence (AI) in academia, concerns have arisen regarding its potential misuse. Using a correlational quantitative approach, data were collected from 104 students through purposive sampling. Two standardized instruments were used to measure self-confidence and academic dishonesty. The results indicated that students had high levels of self-confidence and low tendencies toward academic dishonesty. A significant negative relationship was found between the two variables (r = -0.287, p = 0.003), particularly in the grades and studying dimensions. No gender differences were observed in self-confidence, but a significant difference was found in academic dishonesty between male and female students. This study offers important insights into the protective role of self-confidence against unethical behavior in AI usage and supports the need for implementing digital ethics policies in higher education. ABSTRAK Penelitian ini bertujuan untuk mengkaji hubungan antara self-confidence dan academic dishonesty pada mahasiswa pengguna ChatGPT di perguruan tinggi. Di tengah meningkatnya pemanfaatan teknologi Artificial Intelligence (AI) dalam dunia akademik, muncul kekhawatiran terkait potensi penyalahgunaannya. Dengan menggunakan pendekatan kuantitatif korelasional, data dikumpulkan dari 104 mahasiswa melalui teknik purposive sampling. Pengukuran dilakukan dengan dua skala terstandarisasi: skala self-confidence dan skala academic dishonesty. Hasil analisis menunjukkan bahwa mahasiswa memiliki tingkat self-confidence yang tinggi dan kecenderungan academic dishonesty yang rendah. Terdapat hubungan negatif signifikan antara kedua variabel (r = -0.287, p = 0.003), terutama pada dimensi grades dan studying. Tidak ditemukan perbedaan self-confidence berdasarkan gender, namun terdapat perbedaan signifikan dalam academic dishonesty antara mahasiswa laki-laki dan perempuan. Studi ini memberikan kontribusi penting dalam memahami peran self-confidence sebagai faktor pelindung terhadap perilaku tidak etis dalam penggunaan AI, serta mendorong penerapan kebijakan etika digital dalam pendidikan tinggi.